A study on small and medium-sized accommodation operators in Sabah: Start-up motives, motivational factors and key issues - Quah, Wei Boon (2009)
The paper reports qualitative empirical evidence on the underlying motives and presents motivational factors based on push and pull factors framework for small and medium-sized accommodation. The objectives of the paper are to: (a) explore the underlying motives of individuals and explained by push and pull factors in starting up small and medium-sized accommodation business; (b) explore the factors that motivate individuals to continue operating small and medium-sized accommodation business; (c) highlight the key issues faced by small and medium-sized accommodation operators. In-depth interviews were conducted with 95 small and medium-sized accommodation operators in five administrative divisions in Sabah, Malaysia. The study was adopted a purposive sampling technique based on the population of small and medium-sized accommodation (SMSA) listed by Sabah Tourism Board. The findings reveal eleven underlying motives of individuals in starting up small and medium-sized accommodation business, namely - inherit from family business; potential and opportunity; market demand; own assets; strategic location; influenced by other people (friends and family); profitability; personal and attitude; previous experience in accommodation business; interested in accommodation business and retirement. These start-up motives were categorized into two categories - pull factors (inherit from family business, potential and opportunity; market demand; own assets; strategic location; influenced by other people (friends and family); profitability) and push factor (personal and attitude; previous experience in accommodation business; interested in accommodation business and retirement.) While the factors that motivating SMSA operators to continue operating their business were categorized as seven themes, namely - inherit from family business; market demand; covering operation cost; profitability; interested in accommodation business; potential and opportunity; challenges. The findings of key issues were categorized into external environmental issues, which are: (a) competition, (b) government regulations and policies, (c) seasonal demand issues and (e) financial issues; five internal issues that are related to competition, financial issues, human resource, customer service and satisfaction, and marketing. The paper contributes to the understanding of start-up motives, motivational factors and key issues faced by small and medium-sized accommodation operators in Sabah. It adds to the existing literature on the start-up motives and the issues faced in managing of small and medium-sized accommodation businesses. These findings are significant for the Sabah State Government in order to regulate and set policies for small and medium-sized accommodation businesses.